How wide are European borders? On the integration effects of monetary unions - Axel A. Weber; Guenter Beck (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
We use consumer price data for 81 European cities (in Germany, Austria, Finland, Italy, Spain, Portugal and Switzerland) to study the impact of the introduction of the euro on goods market integration. Employing both aggregated and disaggregated consumer price index (CPI) data we confirm previous results which showed that the distance between European cities explains a significant amount of the variation in the prices of similar goods in different locations. We also find that the variation of relative prices is much higher for two cities located in different countries than for two equidistant cities in the same country. Under the EMU, the elimination of nominal exchange rate volatility has largely reduced these border effects, but distance and border still matter for intra-European relative price volatility.
urn:nbn:de:hebis:30-9849
Keywords: F02; F40; F41; 330; relative price volatility; real exchange rates; law of one price; purchasing power parity; goods market integration; border effects; EMU